Effect of three exercise programs on patients with chronic obstructive pulmonary disease - Dourado, V. Z.; Tanni, S. E. [UNESP]; Antunes, L. C. O. [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Campana, A. O. [UNESP]; Renno, A. C. M.; Godoy, I. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2009)
We compared the effect of three different exercise programs on patients with chronic obstructive pulmonary disease including strength training at 50_80% of one-repetition maximum (1-RM) (ST; N = 11), low-intensity general training (LGT; N = 13), or combined training groups (CT; N = 11). Body composition, muscle strength, treadmill endurance test (TEnd), 6-min walk test (6MWT), Saint George's Respiratory Questionnaire (SGRQ), and baseline dyspnea (BDI) were assessed prior to and after the training programs (12 weeks). The training modalities showed similar improvements (P > 0.05) in SGRQ-total (ST = 13 ± 14%; CT = 12 ± 14%; LGT = 11 ± 10%), BDI (ST = 1.8 ± 4; CT = 1.8 ± 3; LGT = 1 ± 2), 6MWT (ST = 43 ± 51 m; CT = 48 ± 50 m; LGT = 31 ± 75 m), and TEnd (ST = 11 ± 20 min; CT = 11 ± 11 min; LGT = 7 ± 5 min). In the ST and CT groups, an additional improvement in 1-RM values was shown (P < 0.05) compared to the LGT group (ST = 10 ± 6 to 57 ± 36 kg; CT = 6 ± 2 to 38 ± 16 kg; LGT = 1 ± 2 to 16 ± 12 kg). The addition of strength training to our current training program increased muscle strength; however, it produced no additional improvement in walking endurance, dyspnea or quality of life. A simple combined training program provides benefits without increasing the duration of the training sessions.
Keywords: Chronic obstructive pulmonary disease; Exercises; Rehabilitation; Strength training